Unintentional weight loss is the most important indicator of malnutrition among surgical cancer patients - Loh, K.W.; Vriens, M.R.; Gerritsen, A.; Rinkes, I.H.M.B.; van Hillegersberg, R.; Schippers, C.; Steenhagen, E.; Ong, T.A.; Moy, Foong Ming; Molenaar, I.Q. (2012)
Background: Disease-related malnutrition is highly prevalent in hospital patients and varies from 25-40. Early nutritional screening of patients at admission helps to improve recognition of malnourished patients to allow early interventions and enhance clinical outcomes. Method: A total of 104 reoperative surgical patients with oesophageal (34), stomach (17) or pancreatic cancer (53) were recruited in our study. The risk of malnutrition was examined using the quick-and-easy Malnutrition Universal Screening Tool (MUST). Anthropometric data and information on percent weight change over the past six months, unintentional weight loss, dietician referrals, and history of nutritional intervention were collected. Results: A total of 75 of our participants were at high malnutrition risk with a mean (Â±SD) percentage weight loss of 5.18 (Â±6.23), despite a mean BMI of 26.09 (Â±5.73) kgm-2. Participants with a significantly higher percent weight loss, unintentional weight loss, dietician referral and nutritional intervention had a higher risk of malnutrition (p<0.05). Presence of unintentional weight loss was the only significant predictor (OR 3.22; 95 CI 1.23, 8.40) associated with risk of malnutrition after adjusted for all confounders. Conclusion: In conclusion, our findings highlight the importance of routine screening of malnutrition in oncology patients. Medical personnel must be aware that unintentional weight loss is an important predictor of malnutrition risks even if the patientâs BMI is not suggestive of malnutrition.